Communication deficits in a case of a deletion in 7q31.1-q31.33 encompassing FOXP2. - Moreno Campos, Verónica; Benítez-Burraco, Antonio (Clinical Linguistics & Phonetics, 2023)
Copy number variants (CNVs) found in individuals with communication deficits provide a valuable window to the genetic causes of problems with language and, more generally, to the genetic foundation of the human-specific ability to learn and use languages. This paper reports on the language and communication problems of a patient with a microduplication in 22q11.23 and a microdeletion in 7q31.1-q1.33 encompassing FOXP2. The proband exhibits severe speech problems and moderate comprehension deficits, whereas her pragmatic abilities are a relative strength, as she uses gestures quite competently to compensate for her expressive issues. This profile is compatible with the deficiencies found in patients with similar CNVs, particularly with people bearing microdeletions in 7q31.1-q31.33.